First: eliminate fractions - multiply the greatest common denominator with each term which, is... (3*4*p = 12p).
(12p)(1/3p)-(12p)(5) = (12p)(1/4p)
*Cross cancel "like" terms & combine the rest.
(12)(1/3)-(12p)(5) = (12)(1/4)
12/3 - 60p = 12/4
4 - 60p = 3
Sec: combine "like" terms - subtract 4 from both sides (when you move a term to the opposite side, always use the opposite sign).
4-4 - 60p = 3-4
-60p = -1
Third: isolate "p" - divide both sides by -60...
(-60p)/-60 = (-1)/-60
p = 1/60
p = 60
2007-06-15 11:43:21
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
1/(3p) - 5 = 1/(4p)
Actually, it might make more sense to multiply both sides by 3p to get rid of the denominator on the left side... watch what happens.
(3p)1/3p - (3p)5 = (3p)1/4p
By applying the associative and commutative properties of multiplication: (ab)c=a(bc) and ab=ba respectively,
You get
(3)(1/3)(p)(1/p) - (3)(5)(p) = (3)(1/4)(p)(1/p)
Doing the arithmetic, you get
1 - 15p = 3/4
Now, multiply both sides by 4, if you want, to get rid of the 4ths on the right side, but you're going to be stuck with fractions anyway.
Let's go from where we are.
1 - 15p = 3/4
Add -1 to both sides...
-15p = 3/4 - 1 = -1/4
Multiply both sides by -1/15
p = 1/60
If the original equation is (1/3)p - 5 = (1/4)p or
p/3 - 5 = p/4,then multiplying both sides by 12
4p - 60 = 3p
Adding -3p + 60 to both sides
p = 60.
2007-06-15 11:28:55
·
answer #2
·
answered by gugliamo00 7
·
0⤊
0⤋
First, collect all of the terms involving p on the left
and everything else on the right side of the equals sign.
1/3 p - 1/4 p = 5
simplify the two sides as needed:
1/12 p = 5
now, it should be easy to get the answer of p=60
2007-06-15 11:17:09
·
answer #3
·
answered by tfeagin2003 2
·
0⤊
0⤋
The LCD is 12, this would make the problem 4/12p-5=3/12p
Then subtract 4/12p from 3/12p, this would make the problem -5 = -1/12p. Then multiple each side by -12 making it 60 = p.
2007-06-15 11:17:52
·
answer #4
·
answered by Kelly 1
·
0⤊
0⤋
1/3p - 5 = 1/4p
or 1/3p-1/4p=5
or p/12=5
or p=60
2007-06-17 21:24:53
·
answer #5
·
answered by Sumita T 3
·
0⤊
0⤋
multiply both sides by 12 so that you get
4p-60=3p then you can start solving for p
-60= -p
p=60
2007-06-15 11:15:30
·
answer #6
·
answered by Lizzy G 2
·
1⤊
0⤋
1/3p-5=1/4p
Multiply all by 12
4p-60=3p
4p-3p-60=3p-3p
p-60=0
p=60
2007-06-15 12:56:44
·
answer #7
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
a million/15k + 5 = a million/6k -10 a million/15k - a million/6k = -5 -10 a million/15k - a million/6k + 15 = 0 locate the least easy denominator (liquid crystal show) of 15, 6 For 15 and 6, liquid crystal show= 30 1k.....1k......15.....2k - 5k + 450 --- - ------ + ------ = -----------------= 0 15......6.......a million.........30 2k - 5k + 450 = 0 -3k = - 450 ok =a hundred and fifty
2016-10-09 07:13:27
·
answer #8
·
answered by ? 4
·
0⤊
0⤋